Microfinance handbook : an institutional and financial perspective - Ledgerwood, Joanna; Sustainable Banking with the Poor (Project); World Bank (Washington, D.C. : World Bank, 1999)
This handbook provides a comprehensive source for the design, implementation, evaluation, and management of microfinance activities.
At head of title: Sustainable Banking with the Poor.
Includes bibliographical references and index.
osa 08/05/13, ijb 26/02/2019
Ref
Keywords: Microfinance; Financial institutions